Bacteriological analysis of bile in laparoscopic cholecystectomy patients - Koirala, Ashok; Thakur, Dipendra; Agrawal, Sunit; Sharma, Abhilasha (Journal of Nobel Medical College, 2018)
Background: Laparoscopic cholecystectomy is commonly performed operation for symptomatic gall stone disease. The presence of stones within the biliary system is associated with the bacterial colonization of the bile. The aim of this study is to evaluate the bacteriological profile of the bile and to determine appropriate antibiotics for preoperative prophylaxis in laparoscopic cholecystectomy patients. Material & Methods: A prospective study was carried out in NMCTH, Biratnagar from June2017- May 2018. A total of 100 patients admitted through OPD of our hospital for laparoscopic cholecystectomy were studied. About 5ml of bile aspirated from gall bladder was transported to laboratory in sterile syringe for culture and sensitivity. All age groups and both sex were included. Results: Bile culture was positive in 16 patients. The most common organisms isolated from bile was Escherichia coli (50%) followed by Klebsiella species (25%). Histopathological report of all 16 cases revealed chronic cholecystitis. Wound infection was seen in 5% cases and all were bile culture positive. Most sensitive drug was found to be aminoglycoside group followed by piperacilin and tazobactam. Conclusion: Most common organism isolated from bile culture was Escherichia coli. Aminoglycoside group of drugs was found to be more promising compared to other group of drugs. It can be considered as a first line drug for preoperative prophylaxis for patients undergoing laparoscopic cholecystectomy for symptomatic cholelithiasis. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 41-44